2013
DOI: 10.1155/2013/893605
|View full text |Cite
|
Sign up to set email alerts
|

Lesion-Induced Alterations in Astrocyte Glutamate Transporter Expression and Function in the Hippocampus

Abstract: Astrocytes express the sodium-dependent glutamate transporters GLAST and GLT-1, which are critical to maintain low extracellular glutamate concentrations. Here, we analyzed changes in their expression and function following a mechanical lesion in the CA1 area of organotypic hippocampal slices. 6-7 days after lesion, a glial scar had formed along the injury site, containing strongly activated astrocytes with increased GFAP and S100β immunoreactivity, enlarged somata, and reduced capability for uptake of SR101. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 68 publications
(103 reference statements)
0
12
0
Order By: Relevance
“…They exhibit the major advantages of cell cultures such as accessibility and direct control of experimental conditions and, importantly, allow cell‐specific transduction and expression of genetically encoded sensors. While cultured tissue slices are covered by a layer of reactive astrocytes (e.g., Schreiner, Berlinger, Langer, Kafitz, and Rose []), recent studies have established that non‐reactive astrocytes are located in the tissue underneath this outer glial scar, enabling analysis of astrocytic morphology and neuron‐glia interactions (Benediktsson, Schachtele, Green, & Dailey, ; Haber, Zhou, & Murai, ). Moreover, astrocytes in organotypic slices retain their capacity to selectively take up the vital maker SR101 (sulforhodamine 101) (Kafitz, Meier, Stephan, & Rose, ; Nimmerjahn & Helmchen, ; Schreiner et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They exhibit the major advantages of cell cultures such as accessibility and direct control of experimental conditions and, importantly, allow cell‐specific transduction and expression of genetically encoded sensors. While cultured tissue slices are covered by a layer of reactive astrocytes (e.g., Schreiner, Berlinger, Langer, Kafitz, and Rose []), recent studies have established that non‐reactive astrocytes are located in the tissue underneath this outer glial scar, enabling analysis of astrocytic morphology and neuron‐glia interactions (Benediktsson, Schachtele, Green, & Dailey, ; Haber, Zhou, & Murai, ). Moreover, astrocytes in organotypic slices retain their capacity to selectively take up the vital maker SR101 (sulforhodamine 101) (Kafitz, Meier, Stephan, & Rose, ; Nimmerjahn & Helmchen, ; Schreiner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, astrocytes in organotypic slices retain their capacity to selectively take up the vital maker SR101 (sulforhodamine 101) (Kafitz, Meier, Stephan, & Rose, ; Nimmerjahn & Helmchen, ; Schreiner et al, ). This is in contrast to hypertrophic astrocytes located in the outer glial scar of these cultures, which loose SR101 labeling (Schreiner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, maslinic acid slightly elevated GFAP levels after ischemia compared with vehicle treatment, indicating the involvement of maslinic acid in the functional role of reactive astrocytes. Moreover, it has been demonstrated that moderately reactive astrocytes maintain overall glutamate transporter expression and function, which contribute to decreased extracellular glutamate concentrations and prevent excitotoxic cell damage [25]. However, maslinic acid did not affect GFAP activation when it was given to rats not subjected to MCAO, suggesting that maslinic acid had few effects on glial function under normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to consider all cell types present that contribute to the ongoing cell death, degeneration, and inhibition of regeneration. Astrocytes exhibit distinct responses to brain injury, and are a key player in several components of secondary injury including inflammation, 23,34 excitotoxicity, 35 and free radical-mediated injury. 36,37 Here, we focus on the role of these cells in mediating the neuroinflammatory component of secondary injury.…”
Section: Discussionmentioning
confidence: 99%